SECURITY CHALLENGES AND THE SURVIVAL OF DEMOCRACY IN NIGERIA: AN ASSESSMENT OF NIGER EAST SENATORIAL DISTRICT, NIGER STATE - Danjuma Izom, Yahuza (UI Scholars Hub, 2023)
The study assessed security challenges in relation to survival of democracy in Nigeria with focus on Niger East Senatorial District. The methodology adopted for the study is descriptive research. The population of the study was drawn from nine local government areas that constituted the district with a population of 1,513,469 (NPC, 2006). Sample size of 380 was used and the sampling technique was simple random sampling technique. Questionnaire was used as the research instrument which was well structured in two parts. Part (A) is the biodata of the respondent and part (B) was on the subject matter of the research using four likert scale of grading. Method of data collection was basically primary and secondary sources. Theoretical framework of the research is fragile state models. Method of data analysis, the data collected from the field was subjected to tabulation, frequency and percentage. Chi-Square was applied in testing hypotheses. The findings revealed that serious security challenges existed, threatening the survival of democracy in Nigeria. The study has proven that there existed in the Niger East senatorial district Boko Haram, kidnapping, and Fulani Cattle Rustlers among others. It was recommended that government make plans for enough personnel to ensure the safety of the populace and for the need to address our diversity, our mistrust, work together and unite in purpose.